Nurses Knowledge Regarding Nursing Process and Barriers in its Application: Nurses' Knowledge Regarding Nursing Process - Jamal, Zahida; Shaheen, Ghazala; Shaheen, Aziza; Bibi, Nadira; Iqbal, Javed; Sultan, Amir (Pakistan Journal of Health Sciences, 2023)
Nursing process increases patients’ satisfaction and enhances the quality of care provided to patients according to their needs. Objective: To determine the level of knowledge of nurses regarding nursing process and barriers in its application. Methods: The current study used cross-sectional study design for this research project. A self-administered questionnaire to be used to record responses of 80 nurses working in three different teachings hospitals in Peshawar through convenient sampling technique. Frequencies and percentages mean and standard deviation were analyzed through SPSS-20.0 as descriptive statistics. The study was approved by institutional review board while informed consent was taken from each participant. Results: Eighty staff nurses (N=80) completed the survey, where female were in majority (72.5%) In knowledge section, 70% participants answered it as a five-step process which is correct. Of the total, 73.75% answered true by considering the assessment as the data collection part of the nursing process. Moreover, 68.75% participants have a satisfactory knowledge who answered correctly to consider the goals as a part of Planning. 82.50% replied they have access to equipment’s for provision of nursing care while 17.50% has no access to equipment were the barriers in the implementation of nursing process. Conclusions: The study concluded that nursing process is a tool that are implemented for quality care, and most of the participants of the study have knowledge about the nursing process, while lack of facilities for smooth implementation of nursing process was barrier faced by the respondents.